2007
DOI: 10.5511/plantbiotechnology.24.107
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and genetic characterization of transgenic tomato expressing 3-hydroxy-3-methylglutaryl coenzyme A reductase

Abstract: Mevalonic acid (MVA) pathway, in parallel with methylerythritol phosphate (MEP) pathway, produces precursor metabolites for isoprenoids, and affect fruit development in plants. 3-Hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) is supposed to be a key enzyme in the MVA pathway. To understand the role of HMGR in fruit development, we previously generated transgenic tomato (Solanum lycopersicum) expressing a melon HMGR gene (CmHMGR) and observed increased fruit size in these plants. To further examine this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…For example, in melon fruits, the rapid accumulation of HMGR during the early stage of fruit development and the active cell division determine the size of the fruits . However, in tomatoes, while the use of the HMGR inhibitor lovastatin resulted in a significant decrease in the fruit size, the overexpression of the HMGR gene was found to significantly increase the fruit size. , Second, HMGR can directly affect the synthesis of sesquiterpenes and triterpenes. The expression level of HMGR determines the type and content of downstream terpenoid metabolites. , Terpenes are the main components contributing to grape aroma, among which monoterpenes were synthesized by the MEP pathway and sesquiterpenes and triterpenes were synthesized by the MVA pathway, indirectly and directly regulated by HMGR, respectively. , In this study, the suppression and overexpression of HMGR in strawberries changed their aromatic composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in melon fruits, the rapid accumulation of HMGR during the early stage of fruit development and the active cell division determine the size of the fruits . However, in tomatoes, while the use of the HMGR inhibitor lovastatin resulted in a significant decrease in the fruit size, the overexpression of the HMGR gene was found to significantly increase the fruit size. , Second, HMGR can directly affect the synthesis of sesquiterpenes and triterpenes. The expression level of HMGR determines the type and content of downstream terpenoid metabolites. , Terpenes are the main components contributing to grape aroma, among which monoterpenes were synthesized by the MEP pathway and sesquiterpenes and triterpenes were synthesized by the MVA pathway, indirectly and directly regulated by HMGR, respectively. , In this study, the suppression and overexpression of HMGR in strawberries changed their aromatic composition.…”
Section: Discussionmentioning
confidence: 99%
“…57 However, in tomatoes, while the use of the HMGR inhibitor lovastatin resulted in a significant decrease in the fruit size, the overexpression of the HMGR gene was found to significantly increase the fruit size. 56,58 Second, HMGR can directly affect the synthesis of sesquiterpenes and triterpenes. The expression level of HMGR determines the type and content of downstream terpenoid metabolites.…”
Section: ■ Discussionmentioning
confidence: 99%
“…As a result, up-regulation of HMGR genes could improve terpenes productivities in the transgenic plants [23] , [24] , [25] , [26] , [27] . Furthermore, it was reported that transgenic tomato plants that constitutively expressed a heterologous HMGR gene from melon showed a significant increase in fruit size [28] .…”
Section: Introductionmentioning
confidence: 99%
“…when these modified genes are expressed in them (Mandaokar et al, 2000). Tomato is an excellent plant for stably expressing transgenes, indicating a good target for genetic engineering (Kobayashi et al, 2003;Omura et al, 2007;Sun et al, 2007). These characteristics make it an attractive research target for practical application in food and agricultural industries.…”
Section: Insect Bioassaymentioning
confidence: 99%